Targeting the ACE2 receptor using nanomedicine: Novel approach to lung cancer therapy - Sivalingam, Dillon; Singh, Moganavelli (Trends in Immunotherapy, 2023)
The angiotensin-converting enzyme 2 (ACE2) receptor gained prominence in 2020, having been identified as a prime receptor for entry of the novel coronavirus COVID-19, which has led to the current global pandemic. Many stud-ies have reported that lung cancer patients have a higher risk of contracting COVID-19 due to the up-regulated expres-sion of ACE2 in lung cancer cells. Lung cancer is a heterogeneous disease and the most frequently occurring cancer globally. It is more prevalent in men than in women and accounts for an estimated 40% of cancer cases. Over the years, many studies have reported on the ACE2 expression in lung cancer. Conventional methods currently available for the detection and treatment of lung cancer face numerous challenges. Nanomedicine has risen to many challenges facing cancer therapy and drug delivery. With the array of nano delivery systems available, nanomedicine can be used to de-velop alternative methods to help overcome these challenges and improve the therapeutic efficiency in cancer therapy. Hence, this review focuses on lung cancer, the ACE2 receptor, and the use of nanomedicine in formulating a novel tar-geted cancer treatment strategy directed at the ACE2 receptor. This may serve as a stepping stone for exploring further targeting strategies and therapies.